The impact of management option on out-of-pocket costs and perceived financial burden among men with localised prostate cancer in Australia within 6 months of diagnosis - Lindsay, Daniel; Nabukalu, Doreen; Roberts, Matthew J.; Yaxley, John; Quinn, Stephen; Richards, Natalie; FrydenbergK, Mark; Gardiner, Robert; Lawrentschuk, Nathan; Juraskova, Ilona; Murphy, Declan G.; Gordon, Louisa G. (Australian Health Review, 2024)
Objective This study aimed to quantify the out-of-pocket (OOP) costs and perceived financial burden among Australian men with localised prostate cancer in the first 6 months after diagnosis, by primary management option.Methods This cost-analysis quantified OOP costs using administrative claims data and self-reported survey data. Financial burden was assessed using the COmprehensive Score for financial Toxicity–Functional Assessment of Chronic Illness Therapy (COST-FACIT) tool. Participants were recruited into a randomised control trial from public or private treatment centres in Victoria and Queensland. Generalised linear models were used to predict OOP costs and COST-FACIT scores.Results Median total OOP costs within 6 months of diagnosis for 256 Australian patients with localised prostate cancer was A$1172 (A$343–2548). Up to 50% of the sample reported A$0 costs for most medical services. Compared with those managed with active surveillance, men having active treatment had 6.4 (95% CI: 3.2–12.7) times greater total OOP costs. Management option, higher Gleason score at diagnosis and having multiple comorbidities were significant predictors of higher OOP costs. Overall high scores on the COST-FACIT indicated low levels of financial burden for the entire sample.Conclusion Largely attributable to being managed with active surveillance, Australian men diagnosed with localised prostate cancer reported relatively low OOP costs and financial burden in the first 6 months post-diagnosis. Together with clinical outcomes, clinicians can use this up to date evidence on costs and perceived financial burdens to assist localised prostate cancer patients and their families make informed decisions about their preferred management option.